293 Resultsof the first-in-human clinical trial with personalized multi-target adoptive cell therapy (ACTolog IMA101). (9th November 2020) - Tsimberidou, Apostolia; Guenther, Kerstin; Alpert, Amir; Andersson, Borje; Coughlin, Zoe; Fritsche, Jens; Hilf, Norbert; Hwu, Patrick; Kalra, Mamta; Kuttruff-Coqui, Sabrina; Maurer, Dominik; Mendrzyk, Regina; et al.
Abstract : Background: ACTolog (IMA101) is a personalized multi-target adoptive cell therapy (ACT) approach in which autologous T-cell products are redirected against multiple novel defined peptide-HLA (pHLA) cancer targets identified by the target discovery platform XPRESIDENT®. The primary endpoint was to assess the safety of ACTolog. Secondary endpoints were to assess the in vivo persistence of transferred T-cells and antitumor activity (www.clinicaltrials.gov NCT02876510 ). Methods: HLA-A*02:01 positive patients with relapsed/refractory solid tumors whose tumor expressed ≥1 cancer target underwent leukapheresis and endogenous T-cells specific for up to 4 targets were primed and expanded in vitro. Patients received lymphodepletion (fludarabine 40 mg/m² and cyclophosphamide 500 mg/m² on days -6 to -3) followed by up to 4 × 10 10 cells (day 0), and IL-2 (1 × 10 6 IU/m² SC twice daily, 14 days) (Cohort 1). In addition, cohort 2 received atezolizumab (1200 mg IV) every 21 days upon hematologic recovery. Infused T-cells were tracked in patients' blood via flow cytometry-based immunomonitoring as well as TCRβ sequencing. TCRs from target specific T-cells were identified from patients' T-cell products and characterized. Results: From 07/2017–03/2020, 214 patients were screened, and 14 heavily pre-treated patients with various tumor types were infused with 1–3 T-cell products each (table 1 ). The treatment was generally well tolerated. The most common adverse events observed to date were expected cytopenias, mostly attributed to the lymphodepleting regimen, and Grade 1–2 cytokine release syndrome. Prolonged disease stabilization was noted in three patients for 12 months, 12+ months, and 7 months. High frequencies of target-specific T-cells up to 78.7% of CD8+ cells were detected in the blood of treated patients, persisted for >1 year and were detected in post-treatment tumor biopsies. Characterization of individual TCRs contained in T-cell products showed a broad variation of TCR avidities with the majority of TCRs being of low avidity. High-avidity TCRs were identified from products of some patients, including a patient with 26% decrease in tumor measurements 6 weeks post-treatment. Tracking the respective T-cell clonotypes in patients' blood and tumor provides insights into the mechanism of tumor control. Six-month data will be presented at the conference. Conclusions: This is the first reported trial demonstrating the feasibility and tolerability of a personalized ACT approach using multiple defined T-cell products directed to multiple precisely defined pHLA cancer targets. These results support further exploration of a multi-target ACT approach, particularly in the context of T-cells expressing high-avidity TCRs to such defined pHLA targets. Trial Registration: https://clinicaltrials.gov/ct2/show/NCT02876510 Ethics Approval: The study was approved by WCG WIRB, IRB tracking number 20162235. The study was conducted in accordance with the Declaration of Helsinki and the International Conference on Harmonization Good Clinical Practice guidelines. All the study participants provided written informed consent before enrollment. Consent: Patient consent for publication is not required. Patients consented to participate in the study.